Preparation method of conductive metal anti-corrosion coating

By preparing ZIFs/GO/PPY anticorrosion coatings, the problems of traditional corrosion tests and corrosion of metals in acidic environments are solved, and the effect of significantly improving corrosion resistance and extending service life is achieved.

CN119391245AActive Publication Date: 2025-02-07SUZHOU UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411749778.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The traditional corrosion test method takes a long time and is difficult to comprehensively and accurately evaluate the performance of the anticorrosion coating. The metal is prone to corrosion in an acidic environment, which affects the service life and safety of the material.

Method used

Using a method of preparing conductive metal anti-corrosion coating, it is made by graphite powder, concentrated sulfuric acid, potassium permanganate, hydrogen peroxide solution, GO suspension, inorganic salt, imidazole ligand, carbon tube dispersion and propylene epoxy ZIFs/GO/PPY anticorrosion coating is prepared by electrodeposition method to improve the anticorrosion performance of the coating.

Benefits of technology

It significantly improves the corrosion resistance of the surface of the 304 stainless steel, effectively inhibits the corrosion process of metal in acidic environments, extends the service life of metal materials, and provides excellent corrosion resistance and good material synergy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391245A_ABST
    Figure CN119391245A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anti-corrosion coatings, in particular to a preparation method of conductive metal anti-corrosion paint, and the prepared coating can remarkably improve the corrosion resistance of the 304 type stainless steel surface. Compared with uncoated 304SS bare steel, the corrosion potential of 304SS under the protection of the coating is obviously increased, the corrosion current density is obviously reduced, the ZIFs / GO composite material is adopted as epoxy resin coating filler, and PPY is assisted to prepare the anti-corrosion coating. The ZIFs has unique crystal structure and chemical properties, the GO has excellent barrier property and mechanical property, the PPY has good conductivity and oxidation-reduction property, the ZIFs, the GO and the PPY cooperate with one another, so that the coating has better comprehensive performance, and the ZIFs / GO composite material can enhance the binding force between the coating and a matrix and improve the barrier property of the coating at the same time; and the PPY surface layer can further improve the conductivity of the coating and is beneficial to exerting the anodic protection performance in a corrosive environment, so that the matrix metal is better protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion-resistant coatings, and in particular to a method for preparing a conductive metal anti-corrosion coating. Background Art

[0002] Metal corrosion is a common problem that seriously affects the service life and performance of materials. In many industrial fields, such as aerospace, automobile manufacturing, and marine engineering, the corrosion of metal materials can lead to structural damage and equipment failure, which in turn brings huge economic losses and safety hazards. The metal corrosion problem seriously affects the service life and safety of materials. Traditional corrosion test methods are often time-consuming and difficult to fully and accurately evaluate the performance of anti-corrosion coatings. Therefore, an efficient and accurate accelerated metal corrosion test method and a new coating material that can effectively protect metals are needed. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention solves the technical problems by adopting a technical solution: a method for preparing a conductive metal anti-corrosion coating, comprising the following steps:

[0004] Step A, raw material preparation: prepare 1-2 parts of graphite powder, 10-20 parts of concentrated sulfuric acid, 3-5 parts of potassium permanganate, 5-8 parts of hydrogen peroxide solution, 30-100 parts of ionized water, 1-3 parts of inorganic salt, 6-30 parts of imidazole ligand, 3-5 parts of carbon tube dispersion, 1-2 parts of epoxy acrylic resin and 1 part of 304 stainless steel;

[0005] Step B, preparation of auxiliary materials: adding graphite powder to concentrated sulfuric acid and stirring to obtain a mixture, then adding potassium permanganate to the mixture, and continuously stirring during the addition process to obtain a reaction mixture, pouring the reaction mixture into ice water, and adding a hydrogen peroxide solution to terminate the reaction to obtain a termination solution, and filtering the termination solution to produce a filter cake, washing the obtained filter cake with deionized water, and dispersing the washed filter cake in deionized water to obtain a GO suspension;

[0006] Step C, preparation of composite materials: dissolving an inorganic salt and an imidazole ligand in methanol respectively to obtain a solution A and a solution B; then dropping the GO suspension in step B into the solution A and stirring and mixing to obtain a mixed solution, then dropping the solution B into the mixed solution, and after stirring, standing to obtain a composite solution, centrifuging the composite solution obtained by standing to obtain a pre-composite material, then washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a composite material;

[0007] Step D, coating preparation: first, ultrasonically mix the carbon tube dispersion and epoxy acrylic resin to obtain a mixed solution, and place the mixed solution in a stirrer for stirring to obtain a DCE coating, add the composite material prepared in step C to the DCE coating, and ultrasonically mix to obtain a coating slurry, and then apply the coating slurry on the surface of 304 stainless steel, dry to obtain a base coating, and prepare a PPY surface layer on the surface of the base coating by an electrodeposition method, and finally obtain a ZIFs / GO / PPY anti-corrosion coating;

[0008] Step E, performance testing: Use scanning electron microscopy and transmission electron microscopy to analyze the material morphology, and observe the surface micromorphology of the ZIFs / GO / PPY anti-corrosion coating to determine the surface roughness, and then test the conductivity and corrosion resistance to obtain a coating with anti-corrosion effect.

[0009] The present invention is further configured as follows: the preparation of the GO suspension in step B is as follows: step b1: under ice water bath conditions, 10g of graphite powder is added to 200ml of concentrated sulfuric acid, stirring while adding, so that the graphite powder is dispersed in the concentrated sulfuric acid to obtain a mixture; step b2: 30g of potassium permanganate is gradually added to the mixture in step a1, and mixed and stirred to obtain a reaction mixture: step b3: the reaction mixture in step b2 is transferred to a water bath, and the reaction is continued at a temperature of 35-40°C in the water bath for 1-2 hours, and the stirring speed is reduced to 100-200 rpm to obtain a reaction solution; step b4: the reaction solution in step b3 is poured into 1000mL of ice water, and then 50mL of a 30% mass fraction hydrogen peroxide solution is added to terminate the reaction; step b5: the solution in step b4 is filtered using a suction filtration device, and the obtained filter cake is washed 3 times with deionized water; step b6: the filter cake washed in step b5 is dispersed in deionized water, and a GO suspension is formed by ultrasonic mixing for 30 minutes. The optimized Hummers method for preparing GO suspension, including ice-water bath conditions, raw material addition sequence, specific reaction temperature and time, can ensure the stable quality of GO suspension and improve the reliability of subsequent composite material and coating preparation.

[0010] The present invention is further configured that the inorganic salt in step C is zinc nitrate hexahydrate and cobalt nitrate hexahydrate, the imidazole ligand is dimethyl imidazole and dimethylformamide, the composite material is any one of ZIF-67 / GO, ZIF-8 / GO and ZIF-7 / GO, and the preparation steps of ZIF-67 / GO are: solution preparation: dissolving cobalt nitrate hexahydrate and dimethyl imidazole in methanol respectively to obtain solution A and solution B; solution mixing: dropping the GO suspension in step A into solution A and stirring and mixing to obtain a mixed solution, and then dropping solution B The ZIF-67 / GO composite material is prepared by adding the ZIF-67 / GO into the mixed solution and stirring the mixed solution, and then standing the mixed solution to obtain a composite solution; post-treatment: centrifuging the composite solution obtained by standing to obtain a pre-composite material, and then washing the pre-composite material with water and methanol, and placing the washed product in a vacuum oven and drying it to obtain a ZIF-67 / GO composite material; a variety of composite material options (ZIF-67 / GO, ZIF-8 / GO and ZIF-7 / GO) are provided, which enriches the diversity of materials and can be selected according to different needs. Clear preparation steps and parameters ensure the stability of the composite material performance.

[0011] The preparation steps of the ZIF-8 / GO are as follows: solution preparation: zinc nitrate hexahydrate and dimethylimidazole are dissolved in methanol respectively to obtain solution A and solution B; solution mixing: the GO suspension in step A is added dropwise to solution A and stirred to obtain a mixed solution, and then solution B is added dropwise to the mixed solution and stirred, and after the stirring is completed, the solution is allowed to stand to obtain a composite solution; post-treatment: the composite solution obtained by standing is centrifuged to obtain a pre-composite material, and then the pre-composite material is washed with water and methanol, and the washed product is placed in a vacuum oven and dried to obtain a ZIF-8 / GO composite material;

[0012] The preparation steps of the ZIF-7 / GO are as follows: solution preparation: zinc nitrate hexahydrate and dimethylformamide are dissolved in methanol respectively to obtain solution A and solution B; solution mixing: the GO suspension in step A is added dropwise to solution A and stirred to obtain a mixed solution, and then solution B is added dropwise to the mixed solution and stirred, and after the stirring is completed, the solution is allowed to stand to obtain a composite solution; post-treatment: the composite solution obtained by standing is centrifuged to obtain a pre-composite material, and then the pre-composite material is washed with water and methanol, and the washed product is placed in a vacuum oven and dried to obtain a ZIF-7 / GO composite material.

[0013] The present invention is further configured that the preparation of the anti-corrosion coating in step D is as follows: step d1: placing 1.5 g of carbon tube dispersion and 0.5 g of epoxy acrylic resin in an ultrasonic cleaner, ultrasonically mixing to obtain a mixed solution, and placing the mixed solution in a stirrer for stirring to obtain a DCE coating; step d2: adding any one of ZIF-67 / GO, ZIF-8 / GO and ZIF-7 / GO prepared in step C to the DCE coating, placing it in an ultrasonic cleaner for ultrasonic mixing to obtain a coating slurry; step d3: applying the coating slurry on the surface of 304 stainless steel by roller coating, and then The stainless steel sheet after the cloth is placed in an oven and dried to obtain the bottom coating; step d4: take an aqueous solution containing 0.03 mol of pyrrole monomer and 0.05 mol of camphorsulfonic acid as an electrolyte; step d5: prepare the PPY surface layer on the surface of the bottom coating by a constant voltage electrodeposition method, using a three-electrode system, in which the 304SS covering the bottom coating is used as the working electrode, the platinum sheet is used as the counter electrode, and the silver-silver chloride electrode is used as the reference electrode; step d6: electrodeposit the PPY surface layer at a constant voltage potential of +1.4V, and finally obtain the ZIFs / GO / PPY anticorrosion coating by controlling the electrodeposition time. The method of preparing the PPY surface layer by electrodeposition combines a variety of technical means to improve the anticorrosion performance of the coating. The specific preparation steps include ultrasonic mixing, stirring, roller coating and constant voltage electrodeposition, etc., which make the coating preparation process more controllable and precise.

[0014] The present invention is further configured that the step E includes the following steps: step e1: using Fourier infrared spectroscopy, X-ray photoelectron spectroscopy and X-ray diffraction instruments to perform electrochemical impedance spectroscopy tests and potentiodynamic polarization tests on the nanoparticle components, and using scanning electron microscopy and transmission electron microscopy to perform morphological analysis on the materials; step e2: using a scanning electron microscope to observe the surface micromorphology of the prepared ZIFs / GO / PPY anti-corrosion coating, and using an atomic force microscope to determine the roughness of the surface of the ZIFs / GO / PPY anti-corrosion coating; step e3: using a 0.1 mol / L HCl solution to simulate an acidic corrosion environment, and characterizing the conductivity and corrosion resistance of various coating samples through electrochemical tests.

[0015] The present invention is further configured such that the molar ratio of the inorganic salt to the imidazole ligand in the preparation of ZIF-67 / GO in step C is 1:6.5, the molar ratio of the inorganic salt to the imidazole ligand in the preparation of ZIF-8 / GO is 1:10, and the molar ratio of the inorganic salt to the imidazole ligand in the preparation of ZIF-7 / GO is 1:7.

[0016] The present invention is further configured as follows: the stirring time of the mixed solution in step C is 20 minutes, the stirring time of the composite solution is 30 minutes, the static reaction time is 24 hours, the washing times with water and methanol in step B are three times, the vacuum drying temperature is 60°, and the drying time is 24 hours.

[0017] The present invention is further configured that the ultrasonic mixing time of the mixed liquid prepared for the bottom layer in step D is 1 hour, the stirring time of the stirrer is 24 hours, the drying temperature of the stainless steel sheet after coating is 60°C, and the drying time is 24.

[0018] The present invention is further configured such that the electrodeposition time for preparing the surface layer in step d6 is 1200 seconds and the coating thickness is 30 μm.

[0019] The present invention is further configured that the test in step E is performed by a three-electrode system, and the frequency range of the electrochemical impedance spectroscopy test is 10 -2 -10 5 Hz, the amplitude was selected to be 5 mV; the scanning rate of the potentiodynamic polarization test was 1 mV / s.

[0020] The beneficial effects of the present invention are as follows:

[0021] 1. The present invention is provided with an electrochemical test to show that the coating prepared by the present invention can significantly improve the corrosion resistance of the surface of 304 stainless steel. Compared with the uncoated 304SS bare steel, the corrosion potential of the 304SS protected by the coating is significantly increased, and the corrosion current density is significantly reduced. This shows that the coating can effectively inhibit the corrosion process of the metal in an acidic environment and extend the service life of the metal material.

[0022] 2. The present invention adopts ZIFs / GO composite material as epoxy resin coating filler and assists PPY in preparing anti-corrosion coating. ZIFs has unique crystal structure and chemical properties, GO has excellent barrier properties and mechanical properties, and PPY has good conductivity and redox properties. The three work together to make the coating have better comprehensive properties. The ZIFs / GO composite material can enhance the bonding force between the coating and the substrate, while improving the barrier properties of the coating; the PPY surface layer can further improve the conductivity of the coating, which is beneficial to exert the anodic protection performance in a corrosive environment, thereby better protecting the base metal.

[0023] 3. The preparation method of the present invention has reasonable process and relatively simple operation. First, in the preparation process of ZIFs / GO composite materials, by accurately controlling the ratio of raw materials and reaction conditions, high-quality composite materials can be stably prepared. In the preparation of ZIF-67 / GO, ZIF-8 / GO and ZIF-7 / GO, the molar ratio of metal ions to imidazole ligands and reaction temperature, time and other conditions are strictly controlled to ensure the performance consistency of the composite materials. These three materials are respectively composed of different inorganic salts and imidazole ligands, which provide researchers with a variety of choices and can select the most suitable composite materials according to different research needs and application scenarios; secondly, in the coating preparation process, the preparation methods of the bottom coating and the surface coating are both operable, and the process steps such as ultrasound, stirring, roller coating and electrodeposition are easy to control, which is conducive to industrial production.

[0024] 4. The present invention has excellent anti-corrosion performance and good material synergy by setting an anti-corrosion coating, and is expected to have broad application prospects in the field of anti-corrosion of many metal materials. In particular, in the protection of 304 stainless steel, it can effectively solve the problem of its easy corrosion in an acidic environment, and can be applied to the protection of equipment and structures involving the use of 304 stainless steel in industries such as chemical, marine, and construction, reducing maintenance costs and improving the reliability and safety of equipment and structures.

[0025] 5. The present invention provides a method for preparing a conductive metal anti-corrosion coating, which covers the complete process from auxiliary material preparation to coating preparation to performance testing. This enables researchers to conduct metal corrosion research under a unified system, avoids the disconnection between different test links, improves the accuracy and reliability of the test, and uses a variety of advanced testing instruments and methods to comprehensively test the nanoparticle composition, material morphology, coating surface micromorphology, roughness, conductivity and corrosion resistance. This enables researchers to gain an in-depth understanding of the performance characteristics of the anti-corrosion coating, providing a favorable basis for the optimization and improvement of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is an experimental flow chart of the present invention;

[0027] Figure 2 It is a SEM picture in the performance test of the present invention;

[0028] Figure 3 It is a TEM image in the performance test of the present invention;

[0029] Figure 4 It is a potential polarization curve diagram in the performance test of the present invention;

[0030] Figure 5 It is a comparison table in the performance test of the present invention; DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0032] Example 1: Please refer to Figure 1 - Figure 5 The present invention provides a technical solution: a method for preparing a conductive metal anti-corrosion coating, comprising the following steps:

[0033] Step A, raw material preparation: prepare 1-2 parts of graphite powder, 10-20 parts of concentrated sulfuric acid, 3-5 parts of potassium permanganate, 5-8 parts of hydrogen peroxide solution, 30-100 parts of ionized water, 1-3 parts of inorganic salt, 6-30 parts of imidazole ligand, 3-5 parts of carbon tube dispersion, 1-2 parts of epoxy acrylic resin and 1 part of 304 stainless steel;

[0034] Step B, preparation of auxiliary materials: adding graphite powder to concentrated sulfuric acid and stirring to obtain a mixture, then adding potassium permanganate to the mixture, and continuously stirring during the addition process to obtain a reaction mixture, pouring the reaction mixture into ice water, and adding a hydrogen peroxide solution to terminate the reaction to obtain a termination solution, and filtering the termination solution to produce a filter cake, washing the obtained filter cake with deionized water, and dispersing the washed filter cake in deionized water to obtain a GO suspension;

[0035] Step C, preparation of composite materials: dissolving an inorganic salt and an imidazole ligand in methanol respectively to obtain a solution A and a solution B; then dropping the GO suspension in step B into the solution A and stirring and mixing to obtain a mixed solution, then dropping the solution B into the mixed solution, and after stirring, standing to obtain a composite solution, centrifuging the composite solution obtained by standing to obtain a pre-composite material, then washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a composite material;

[0036] Step D, coating preparation: first, ultrasonically mix the carbon tube dispersion and epoxy acrylic resin to obtain a mixed solution, and place the mixed solution in a stirrer for stirring to obtain a DCE coating, add the composite material prepared in step C to the DCE coating, and ultrasonically mix to obtain a coating slurry, and then apply the coating slurry on the surface of 304 stainless steel, dry to obtain a base coating, and prepare a PPY surface layer on the surface of the base coating by an electrodeposition method, and finally obtain a ZIFs / GO / PPY anti-corrosion coating;

[0037] Step E, performance testing: Use scanning electron microscopy and transmission electron microscopy to analyze the material morphology, and observe the surface micromorphology of the ZIFs / GO / PPY anti-corrosion coating to determine the surface roughness, and then test the conductivity and corrosion resistance to obtain a coating with anti-corrosion effect.

[0038] Embodiment 2: Based on Embodiment 1, a method for preparing a conductive metal anti-corrosion coating comprises the following steps:

[0039] Step A, raw material preparation: prepare 1-2 parts of graphite powder, 10-20 parts of concentrated sulfuric acid, 3-5 parts of potassium permanganate, 5-8 parts of hydrogen peroxide solution, 30-100 parts of ionized water, 1-3 parts of inorganic salt, 6-30 parts of imidazole ligand, 3-5 parts of carbon tube dispersion, 1-2 parts of epoxy acrylic resin and 1 part of 304 stainless steel;

[0040] Step B, preparation of auxiliary materials: adding graphite powder to concentrated sulfuric acid and stirring to obtain a mixture, then adding potassium permanganate to the mixture, and continuously stirring during the addition process to obtain a reaction mixture, pouring the reaction mixture into ice water, and adding a hydrogen peroxide solution to terminate the reaction to obtain a termination solution, and filtering the termination solution to produce a filter cake, washing the obtained filter cake with deionized water, and dispersing the washed filter cake in deionized water to obtain a GO suspension;

[0041] Step C, preparation of composite materials: dissolving an inorganic salt and an imidazole ligand in methanol respectively to obtain a solution A and a solution B; then dropping the GO suspension in step B into the solution A and stirring to obtain a mixed solution, then dropping the solution B into the mixed solution, and after stirring, standing to obtain a composite solution, centrifuging the composite solution obtained by standing to obtain a pre-composite material, and then washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a composite material.

[0042] Step D, coating preparation: firstly, the carbon tube dispersion liquid and the epoxy acrylic resin are ultrasonically mixed to obtain a mixed solution, and the mixed solution is placed in a stirrer for stirring to obtain a DCE coating, the composite material prepared in step C is added to the DCE coating, and ultrasonically mixed to obtain a coating slurry, and then the coating slurry is coated on the surface of 304 stainless steel, and dried to obtain a ZIF-67 / Go coating;

[0043] Embodiment 3: Based on Embodiment 1, a method for preparing a conductive metal anti-corrosion coating comprises the following steps:

[0044] Step A, raw material preparation: 1-3 parts of inorganic salt, 6-30 parts of imidazole ligand, 3-5 parts of carbon tube dispersion, 1-2 parts of epoxy acrylic acid resin and 1 part of 304 stainless steel;

[0045] Step B, preparation of composite materials: dissolving an inorganic salt and an imidazole ligand in methanol respectively to obtain a solution A and a solution B, then dropping the solution B into the solution A, stirring and standing to obtain a composite solution, centrifuging the composite solution obtained by standing to obtain a pre-composite material, then washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a composite material.

[0046] Step C, coating preparation: firstly, the carbon tube dispersion liquid and the epoxy acrylic resin are ultrasonically mixed to obtain a mixed liquid, and the mixed liquid is placed in a stirrer for stirring to obtain a DCE coating, the composite material prepared in step C is added to the DCE coating, and ultrasonically mixed to obtain a coating slurry, and then the coating slurry is coated on the surface of 304 stainless steel, and dried to obtain a bottom coating;

[0047] Step D, performance testing: Use scanning electron microscopy and transmission electron microscopy to analyze the material morphology, and observe the surface micromorphology of the resin coating containing ZIF-67 to determine the surface roughness, and then test the conductivity and corrosion resistance.

[0048] Performance testing:

[0049] When used, coatings were prepared according to the methods of Example 1, Example 2 and Example 3 as Experimental Group 1, Experimental Group 2 and Experimental Group 3, respectively, and coatings prepared from 304 stainless steel bare steel and pure resin coating were taken as Control Group 1 and Control Group 2 for testing;

[0050] The test results can be obtained through Figure 2 The SEM and TEM images of ZIF-67 (a1-a3) and ZIF-67 / GO (b1-b3) were observed. Figure 3The SEM and AFM images of pure resin coating (a1-a2), resin coating containing ZIF-67 filler (b1-b2), resin coating containing ZIF-67 / GO filler (c1-c2) and ZIF-67 / GO / PPY were compared. Then, experimental group 1, experimental group 2, experimental group 3, control group 1 and control group 2 were placed in a corrosion environment simulated by 0.1 mol / L HCl solution for comparison. Figure 4 and through Figure 5 is the result of potentiodynamic polarization of 304 stainless steel bare steel and four coatings in 0.1 mol / L HCl solution. E is obtained by Tafel extrapolation fitting. corr andi corr Specific parameters such as Figure 5 As shown in Table 1, the E of 304SS bare steel corr and i corr The values ​​are -0.41V and 2.36×10 -5 A.cm 2 , while all coatings protect the 304SS E corr The E of the ZIF-67 / GO / PPY coating layer containing both the ZIF-67 / GO / PPY filler and the PPY surface layer was significantly increased. corr The value is the highest, indicating that the presence of the coating significantly reduces the corrosion rate of 304SS and significantly improves its corrosion resistance. corr On the contrary, this special polarization phenomenon is increased, which is a special phenomenon caused by the good redox ability of PPY itself. The polarization data of the PPY sample are obtained by Tafel extrapolation method. corr It is the sum of the current density generated by the redox reaction in the coating and the dissolution of the matrix. It can be considered that the i of the PPY coating sample is corr Most of it is produced by redox reactions. redox The matrix dissolution actually produces redox Very small, the coating has excellent corrosion protection effect.

[0051] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A method for preparing a conductive metal anti-corrosion coating, characterized in that: The following steps are involved: Step A, raw material preparation: prepare 1-2 parts of graphite powder, 10-20 parts of concentrated sulfuric acid, 3-5 parts of potassium permanganate, 5-8 parts of hydrogen peroxide solution, 30-100 parts of ionized water, 1-3 parts of inorganic salt, 6-30 parts of imidazole ligand, 3-5 parts of carbon tube dispersion, 1-2 parts of epoxy acrylic resin and 1 part of 304 stainless steel; Step B, preparation of auxiliary materials: adding graphite powder to concentrated sulfuric acid and stirring to obtain a mixture, then adding potassium permanganate to the mixture, and continuously stirring during the addition process to obtain a reaction mixture, pouring the reaction mixture into ice water, and adding a hydrogen peroxide solution to terminate the reaction to obtain a termination solution, and filtering the termination solution to produce a filter cake, washing the obtained filter cake with deionized water, and dispersing the washed filter cake in deionized water to obtain a GO suspension; Step C, preparation of composite materials: dissolving an inorganic salt and an imidazole ligand in methanol respectively to obtain a solution A and a solution B; then dropping the GO suspension in step B into the solution A and stirring and mixing to obtain a mixed solution, then dropping the solution B into the mixed solution, and after stirring, standing to obtain a composite solution, centrifuging the composite solution obtained by standing to obtain a pre-composite material, then washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a composite material; Step D, coating preparation: first, ultrasonically mix the carbon tube dispersion and epoxy acrylic resin to obtain a mixed solution, and place the mixed solution in a stirrer for stirring to obtain a DCE coating, add the composite material prepared in step C to the DCE coating, and ultrasonically mix to obtain a coating slurry, and then apply the coating slurry on the surface of 304 stainless steel, dry to obtain a base coating, and prepare a PPY surface layer on the surface of the base coating by an electrodeposition method, and finally obtain a ZIFs / GO / PPY anti-corrosion coating; Step E, performance testing: Use scanning electron microscopy and transmission electron microscopy to analyze the material morphology, and observe the surface micromorphology of the ZIFs / GO / PPY anti-corrosion coating to determine the surface roughness, and then test the conductivity and corrosion resistance to obtain a coating with an anti-corrosion effect.

2. The method for preparing a conductive metal anti-corrosion coating according to claim 1, characterized in that: The preparation of the GO suspension in step B is as follows: Step b1: In an ice water bath, add 10 g of graphite powder to 200 ml of concentrated sulfuric acid, stirring while adding to disperse the graphite powder in the concentrated sulfuric acid to obtain a mixture; Step b2: gradually add 30 g of potassium permanganate to the mixture in step a1, and mix and stir to obtain a reaction mixture: Step b3: transferring the reaction mixture in step b2 to a water bath, continuing the reaction in the water bath at a temperature of 35-40° C. for 1-2 hours, and reducing the stirring speed to 100-200 rpm to obtain a reaction solution; Step b4: pour the reaction solution in step b3 into 1000 mL of ice water, and then add 50 mL of 30% by mass hydrogen peroxide solution to terminate the reaction; Step b5: Filter the solution in step b4 using a suction filtration device, and wash the obtained filter cake with deionized water three times; Step b6: The filter cake washed in step b5 was dispersed in deionized water and ultrasonically mixed for 30 minutes to form a GO suspension.

3. The method for preparing a conductive metal anti-corrosion coating according to claim 1, characterized in that: In step C, the inorganic salt is zinc nitrate hexahydrate and cobalt nitrate hexahydrate, the imidazole ligand is dimethylimidazole and dimethylformamide, the composite material is any one of ZIF-67 / GO, ZIF-8 / GO and ZIF-7 / GO, and the preparation steps of ZIF-67 / GO are: Solution preparation: dissolve cobalt nitrate hexahydrate and dimethylimidazole in methanol to obtain solution A and solution B respectively; Solution mixing: the GO suspension in step A is added dropwise to solution A and stirred to obtain a mixed solution, and then solution B is added dropwise to the mixed solution and stirred, and after the stirring is completed, the solution is allowed to stand to obtain a composite solution; Post-treatment: centrifuging the composite solution obtained by standing to obtain a pre-composite material, washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a ZIF-67 / GO composite material; The preparation steps of the ZIF-8 / GO are: Solution preparation: Dissolve zinc nitrate hexahydrate and dimethylimidazole in methanol to obtain solution A and solution B respectively; Solution mixing: the GO suspension in step A is added dropwise to solution A and stirred to obtain a mixed solution, and then solution B is added dropwise to the mixed solution and stirred, and after the stirring is completed, the solution is allowed to stand to obtain a composite solution; Post-treatment: centrifuging the composite solution obtained by standing to obtain a pre-composite material, washing the pre-composite material with water and methanol, placing the washed product in a vacuum oven, and drying to obtain a ZIF-8 / GO composite material; The preparation steps of the ZIF-7 / GO are: Solution preparation: Dissolve zinc nitrate hexahydrate and dimethylformamide in methanol to obtain solution A and solution B respectively; Solution mixing: the GO suspension in step A is added dropwise to solution A and stirred to obtain a mixed solution, and then solution B is added dropwise to the mixed solution and stirred, and after the stirring is completed, the solution is allowed to stand to obtain a composite solution; Post-treatment: The composite solution obtained by standing is centrifuged to obtain a pre-composite material, and then the pre-composite material is washed with water and methanol. The washed product is placed in a vacuum oven and dried to obtain a ZIF-7 / GO composite material.

4. The method for preparing a conductive metal anti-corrosion coating according to claim 1, characterized in that: The preparation of the anticorrosive coating in step D is as follows: Step d1: placing 1.5 g of carbon tube dispersion and 0.5 g of epoxy acrylic resin in an ultrasonic cleaner, performing ultrasonic mixing to obtain a mixed solution, and placing the mixed solution in a stirrer for stirring to obtain a DCE coating; Step d2: adding any one of the ZIF-67 / GO, ZIF-8 / GO and ZIF-7 / GO prepared in step C to the DCE coating, placing the mixture in an ultrasonic cleaner for ultrasonic mixing to obtain a coating slurry; Step d3: coating the coating slurry on the surface of 304 stainless steel by roller coating, and then placing the coated stainless steel sheet in an oven to dry to obtain a bottom coating; Step d4: taking an aqueous solution containing 0.03 mol of pyrrole monomer and 0.05 mol of camphorsulfonic acid as an electrolyte; Step d5: a PPY surface layer was prepared on the surface of the bottom coating layer by a constant voltage electrodeposition method, using a three-electrode system, wherein the 304SS covering the bottom coating layer was used as a working electrode, a platinum sheet was used as a counter electrode, and a silver-silver chloride electrode was used as a reference electrode; Step d6: Electrodeposit the PPY surface layer at a constant voltage potential of +1.4 V, and finally obtain the ZIFs / GO / PPY anti-corrosion coating by controlling the electrodeposition time.

5. The method for preparing a conductive metal anti-corrosion coating according to claim 1, characterized in that: The step E comprises the following steps: Step e1: using Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and X-ray diffraction instruments to perform electrochemical impedance spectroscopy and potentiodynamic polarization tests on the nanoparticle components, and using scanning electron microscopy and transmission electron microscopy to perform morphological analysis on the materials; Step e2: using a scanning electron microscope to observe the surface micromorphology of the prepared ZIFs / GO / PPY anti-corrosion coating, and using an atomic force microscope to determine the surface roughness of the ZIFs / GO / PPY anti-corrosion coating; Step e3: Using 0.1 mol / L HCl solution to simulate an acidic corrosion environment, the conductivity and corrosion resistance of various coating samples were characterized by electrochemical testing.

6. The method for preparing a conductive metal anti-corrosion coating according to claim 3, characterized in that: The molar ratio of the inorganic salt to the imidazole ligand in the preparation of ZIF-67 / GO in step C is 1:6.5, the molar ratio of the inorganic salt to the imidazole ligand in the preparation of ZIF-8 / GO is 1:10, and the molar ratio of the inorganic salt to the imidazole ligand in the preparation of ZIF-7 / GO is 1:

7.

7. The method for preparing a conductive metal anti-corrosion coating according to claim 3, characterized in that: The stirring time of the mixed solution in step C is 20 minutes, the stirring time of the composite solution is 30 minutes, the static reaction time is 24 hours, the washing times with water and methanol in step B are three times, the vacuum drying temperature is 60°, and the drying time is 24 hours.

8. The method for preparing a conductive metal anti-corrosion coating according to claim 4, characterized in that: The ultrasonic mixing time of the mixed liquid prepared for the bottom layer in step D is 1 hour, the stirring time of the stirrer is 24 hours, the drying temperature of the stainless steel sheet after coating is 60° C., and the drying time is 24.

9. The method for preparing a conductive metal anti-corrosion coating according to claim 4, characterized in that: The electrodeposition time for preparing the surface layer in step d6 is 1200 seconds, and the coating thickness is 30 μm.

10. The method for preparing a conductive metal anti-corrosion coating according to claim 4, characterized in that: The test in step E is performed by a three-electrode system, and the frequency range of the electrochemical impedance spectroscopy test is 10 -2 -10 5 Hz, the amplitude was selected to be 5 mV; the scanning rate of the potentiodynamic polarization test was 1 mV / s.

Citation Information

Patent Citations

  • Modified epoxy anticorrosive coating, and preparation method and application thereof

    CN111363450A

  • Preparation method and application of polypyrrole-coated ZIF-8 modified epoxy resin anticorrosive paint

    CN114591671A

  • Intelligent metal frame-conductive polymer anticorrosive coating and preparation method and application thereof

    CN116145206A

  • Antibacterial and anticorrosive difunctional powder as well as preparation method and application thereof

    CN116554495A

  • ZIF / GO-based synergistic corrosion inhibition filler as well as preparation method and application thereof

    CN118546554A